Resveratrol Modulates the Gut-Brain Axis: Focus on Glucagon-Like Peptide-1, 5-HT, and Gut Microbiota - Chung, Ji Yeon; Jeong, Jae-Ho; Song, Juhyun (Frontiers in Aging Neuroscience, 2020)
Resveratrol is a natural polyphenol that has anti-aging and anti-inflammatory properties against stress condition. It reported that resveratrol has beneficial functions in various metabolic and central nervous system (CNS) diseases, such as obesity, diabetes, depression, and dementia. Recently, many researchers have emphasized the connection between the brain and gut, called the gut-brain axis, for treating both CNS neuropathologies and gastrointestinal diseases. Based on previous findings, resveratrol is involved in glucagon like peptide 1 (GLP-1) secreted by intestine L cells, the patterns of microbiome in the intestine, the 5-Hydroxytryptamine (5-HT) level, and CNS inflammation. Here, we review recent evidences concerning the relevance and regulatory function of resveratrol in the gut-brain axis from various perspectives. Here, we highlight the necessity for further study on resveratrol’s specific mechanism in the gut-brain axis. We provides the potential of resveratrol that it is a natural therapeutic substance for treating both neuropathology and gastrointestinal dysfunction.